Alpha-synuclein pathology enhances peripheral and CNS immune responses to bacterial endotoxins - Anna-Sophia Hartke; Cara S. Schreiber; Kristina Lau; Ivo Wiesweg; Inken Waltl; Ulrich Kalinke; Franziska Richter; Christopher Käufer (Neurobiology of Disease)
Increasing evidence points to infectious diseases as contributor to the pathogenesis of neurodegeneration in Parkinson's disease (PD), probably driven by a peripheral and CNS inflammatory response together with alpha-synuclein (aSyn) pathology. Pro-inflammatory lipopolysaccharide (LPS) endotoxin is suggested as a risk factor, and LPS shedding gram-negative bacteria are more prevalent in the gut-microbiome of PD patients. Here, we investigated whether LPS could contribute to the neurodegenerative disease progression via neuroinflammation, especially under conditions of aSyn pathology. To investigate this, we created a double-hit model based on the Thy1-aSyn mouse line (line 61), an established aSyn-overexpression model of PD, exposed to a single intraperitoneal injection of LPS at a dose of 0.8 mg/kg (equivalent to approximately 1,200,000 EU/kg). Clinical parameters, flow cytometry of blood and immune cells in the brain, brain immunohistology and motor behavior were evaluated over time. As expected, the LPS dosage induced transient acute symptoms and mild weight loss in mice, with full recovery after 7 days. In aSyn over-expressing mice, this single low dose of LPS was sufficient to alter the expression of specific markers on blood and brain immune cells and induced brain region-specific microgliosis that were present at 7 days post LPS injection. At 14 days post injection of LPS, aSyn expression was reduced in wild-type mice, indicating a specific response of the endogenous protein to the endotoxin. At this early time point, motor behavior is not yet robustly impacted by the observed pathological alterations. In conclusion, aSyn pathology renders the peripheral and central immune response more sensitive to a single low dose of bacterial endotoxin, which mimics a transient dysbiosis or gut infection. Thus, this data suggests that such peripheral triggers should be monitored in PD patients for instance by blood immune cell response as biomarkers. Furthermore, results from this study lend further support to the development of treatments aiming to reduce the impact of bacterial dysbiosis as a promising strategy to mitigate PD progression.